Cortical Bone Porosity in Rabbit Models of Osteoporosis - Harrison, Kim D (J Bone Miner Res, 2020)
Cortical bone porosity is intimately linked with remodeling, is of growing clinical interest, and is increasingly accessible by imaging. Thus, the potential of animal models of osteoporosis (OP) to provide a platform for studying how porosity develops and responds to interventions is tremendous. To date, rabbit models of OP have largely focused on trabecular microarchitecture or bone density; some such as ovariectomy (OVX) have uncertain efficacy and cortical porosity has not been extensively reported. Our primary objective was to characterize tibial cortical porosity in rabbit‐based models of OP, including OVX, glucocorticoids (GC), and OVX + GC relative to controls (SHAM). We sought to: (i) test the hypothesis that intracortical remodeling is elevated in these models; (ii) contrast cortical remodeling and porosity in these models with that induced by parathyroid hormone (1–34; PTH); and (iii) contrast trabecular morphology in the proximal tibia across all groups. Evidence that an increase in cortical porosity occurred in all groups was observed, although this was the least robust for GC. Histomorphometric measures supported the hypothesis that remodeling rate was elevated in all groups and also revealed evidence of uncoupling of bone resorption and formation in the GC and OVX + GC groups. For trabecular bone, a pattern of loss was observed for OVX, GC, and OVX + GC groups, whereas the opposite was observed for PTH. Change in trabecular number best explained these patterns. Taken together, the findings indicated rabbit models provide a viable and varied platform for the study of OP and associated changes in cortical remodeling and porosity. Intriguingly, the evidence revealed differing effects on the cortical and trabecular envelopes for the PTH model. © 2020 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR)..